2003
DOI: 10.1118/1.1567735
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of cell repopulation on the tumor response to fractionated external radiotherapy

Abstract: In this work we study the descriptive power of the main tumor control probability (TCP) models based on the linear quadratic (LQ) mechanism of cell damage with cell recovery. The Poisson, binomial, and a dynamic TCP model, developed recently by Zaider and Minerbo are considered. The Zaider-Minerbo model takes cell repopulation into account. It is shown that the Poisson approximation incorporating cell repopulation is conceptually incorrect. Based on the Zaider-Minerbo model, an expression for the TCP for fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 24 publications
5
34
0
Order By: Relevance
“…We followed the formalism outlined by Warkentin et al [21], originally published by Zaider and Minerbo [22] and subsequently extended for fractionated delivery by Stavreva et al [23]. The model includes linear-quadratic (LQ) cell kill and repopulation and is based on the following input parameters: …”
Section: Modeling Of Tumor Control Probabilitymentioning
confidence: 99%
“…We followed the formalism outlined by Warkentin et al [21], originally published by Zaider and Minerbo [22] and subsequently extended for fractionated delivery by Stavreva et al [23]. The model includes linear-quadratic (LQ) cell kill and repopulation and is based on the following input parameters: …”
Section: Modeling Of Tumor Control Probabilitymentioning
confidence: 99%
“…Since the number of FSUs is always quite large, the cumulative binomial distribution in Eq. (4) can be approximated by a cumulative normal distribution (14) : NTCP=Φ(N(pFSU(D)normalμcr)pFSU(D)(1pFSU(D))), where the Φ (probit) function is as defined in Eq. (2).…”
Section: Methodsmentioning
confidence: 99%
“…In a recent PhD thesis, Gong [21] included cancer stem cells into the TCP models and she confirmed that it is critical to control the stem cells for treatment to be successful. First studies have shown that the above TCP models are powerful tools in the prediction and planning of radiation treatments ( [22,61]), however, further studies of their qualitative properties and further data analysis is needed.…”
Section: Tumor Control and Treatmentmentioning
confidence: 99%
“…The mathematical framework comes directly from ecological applications, but the interpretations, and some of the details are specific to cancer modelling. This direction of research has blossomed in beautiful theories on brith-death processes and branching processes, which are able to include cell cycle dynamics and differential radiosensitivities depending on the cell cycle state (see [22,25,26,31,43,61,66]). In a recent PhD thesis, Gong [21] included cancer stem cells into the TCP models and she confirmed that it is critical to control the stem cells for treatment to be successful.…”
Section: Tumor Control and Treatmentmentioning
confidence: 99%